Economical aspect of Turkish sports federations before and after gaining autonmy (the case of Voleyball Federation of Turkey) - Bülent Fısekcıoglu; Ezgi Ertuzun (Selcuk University, 2013)
In this study, where financial construction of Turkish Sports Federations before and after gaining autonomy iscompared with the case of Volleyball Federation of Turkey, the financial contribution of autonomy process,which was legalized in 2004 to serve as a solution, to the federations is evaluated and recommendations forsolution are tried to be developed. Financial information on Volleyball Federation of Turkey's being autonomousis examined using the method of "documentation" and the findings obtained as a result are illustrated on tablesand graphics. Economical aspect of autonomy stems from the fact that autonomous federations have financialautonomy. Federations use several methods in order to be financially autonomous and self-sufficientorganizations. In this respect, Football Federation and federations in Europe which have the experience ofautonomy constitute a model and it is observed that they are successful in this point.